2022
DOI: 10.1055/s-0042-1742521
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Informatics 2022: Real-World Data Yields Important Insights into the Conduct of Clinical Trials and Registries

Abstract: Objective: To summarize significant research contributions on cancer informatics published in 2021. Methods: An extensive search using PubMed/MEDLINE and Altmetric scores was conducted to identify the scientific contributions published in 2021 that address topics in cancer informatics. The selection process comprised three steps: (i) 15 candidate best papers were first selected by the two section editors, (ii) external reviewers from internationally renowned research teams reviewed each candidate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…They concluded that care will be needed to ensure that algorithmic bias does not magnify existing disparities. "Real-world data yields important insights into the conduct of clinical trials and registries", concluded Debra Patt and Jeremy Warner, co-editors of the CI section, in their review of scientific contributions published in 2021 on topics related to cancer informatics [40]. Indeed, the two selected best papers deal with complementary aspects of real-world databases and registries for population-level research in cancer [41,42].…”
Section: Highlights Of the 31 St Edition Of The Imia Yearbookmentioning
confidence: 99%
“…They concluded that care will be needed to ensure that algorithmic bias does not magnify existing disparities. "Real-world data yields important insights into the conduct of clinical trials and registries", concluded Debra Patt and Jeremy Warner, co-editors of the CI section, in their review of scientific contributions published in 2021 on topics related to cancer informatics [40]. Indeed, the two selected best papers deal with complementary aspects of real-world databases and registries for population-level research in cancer [41,42].…”
Section: Highlights Of the 31 St Edition Of The Imia Yearbookmentioning
confidence: 99%